Construction of a Religious Moderation Measuring Tool for Student of Mataram State Islamic University - Baiq Arwindy Prayona; Gemuh Surya Wahyudi (Universitas Islam Negeri (UIN) Mataram, 2023)
The purpose of this study is to construct a measuring instrument for religious moderation as a tool that can be used to detect the level of religious moderation in students so that interventions to increase the level of religious moderation in UIN Mataram students can be more targeted. The preparation of this scale uses quantitative methods with a psychometric approach. This research produces a measuring tool for religious moderation for UIN Mataram students in the format of a measuring scale called the Moderama Scale. The Moderama Scale is made with a Likert scale model consisting of five response options with a favourable aitem format. The number of items in this scale is 25 items from four aspects of religious moderation. This Moderama Scale can be used to measure the level of religious moderation of students because it has met the valid and reliable requirements.